References to jurisprudence of foreign constitutional courts in judgments and decisions of the Constitutional Tribunal of the Republic of Poland - Maroń, Grzegorz (Review of European and Comparative Law, 2022)
In its jurisprudence, the Constitutional Tribunal of the Republic of Poland often uses the comparative law method. For it, the comparative material is not only the normative acts in force in other countries, but also foreign jurisprudence. The article presents the results of a quantitative and qualitative study of the judgments of the Polish Constitutional Tribunal in terms of the presence of references to the judgments of other constitutional courts. Reference by the Tribunal to foreign constitutional jurisprudence is a relatively rare practice, but not an occasional one. It was intensified after Poland's accession to the European Union. Although the main point of reference for the Tribunal in its comparative analysis is still the jurisprudence of the German Federal Constitutional Court and constitutional courts of other Western countries, it also increasingly frequently reaches to the judgments of the constitutional courts of Central European and Baltic countries. The subject issue is part of the progressive process of the so-called transnational judicial discourse or judicial globalization. The reluctance of the Tribunal to reach in its rulings to judgments of foreign constitutional courts, which has been observed since 2017, may be the beginning of its assumption of an exceptionalistic attitude similar to the U.S. Supreme Court.